Zinc diffusion composite passivation solution, preparation method and passivation process

CN123005366APending Publication Date: 2026-10-30SHANXI TIANJU HENGXIN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004352.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

渗锌层虽然硬度高、耐磨性好,但单有渗锌层的工件在潮湿、氯离子含量高的恶劣环境中(如煤矿井下)仍存在一定的腐蚀风险

Benefits of technology

复合钝化液通过磷酸二氢锌、85%磷酸和硝酸锌复配,在促进剂和络合剂作用下,形成致密均匀的磷化膜,结合季铵化木质素促进锌离子实现均匀、平整的沉积,避免局部过度沉积,从而抑制锌枝晶的生长,进一步形成平整、致密的防腐外膜,季铵化木质素静电吸附在金属工件表面,还提升了工件在潮湿、酸性或高氯离子环境中的耐腐蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a zinc diffusion composite passivation solution, which comprises, with the total mass of the main components being 100 parts, 30-40 parts of zinc dihydrogen phosphate, 3-5 parts of 85% phosphoric acid, 8-15 parts of zinc nitrate, 0.1-0.3 parts of quaternary ammonium lignin, 0.2-0.5 parts of an accelerator, 1-2 parts of a complexing agent and the rest water. The composite passivation solution is prepared by compounding zinc dihydrogen phosphate, 85% phosphoric acid and zinc nitrate, and under the action of the accelerator and the complexing agent, a dense and uniform phosphating film is formed; the quaternary ammonium lignin promotes the uniform and smooth deposition of zinc ions, avoids local excessive deposition, thereby inhibits the growth of zinc dendrites, further forms a smooth and dense anticorrosion outer film, and the quaternary ammonium lignin is electrostatically adsorbed on the surface of the metal workpiece, and the corrosion resistance of the workpiece in a humid, acidic or high-chloride-ion environment is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal surface treatment technology, specifically to a zinc diffusion composite passivation solution, its preparation method, and passivation process. Background Technology

[0002] Surface treatment of metals and alloys is an effective way to improve their corrosion resistance. While chromate surface treatment can improve the corrosion resistance of metal and alloy surfaces, the processes for treating trivalent and hexavalent chromium are highly toxic and cause serious environmental pollution. Zinc diffusion technology, as a mature and reliable metal surface corrosion protection technology, involves mixing steel parts with a zinc diffusion agent and heating them in a zinc diffusion furnace. This allows active zinc atoms to penetrate from the surface into the steel parts, forming a zinc-iron alloy layer on their surface. This layer has advantages such as strong adhesion, good wear resistance, and no hydrogen embrittlement. Although the zinc diffusion layer has high hardness and good wear resistance, workpieces with only a zinc diffusion layer still face a certain risk of corrosion in harsh environments with high humidity and high chloride ion content (such as underground coal mines). Summary of the Invention

[0003] One of the objectives of this invention is to overcome the deficiencies in the prior art and provide a zinc diffusion composite passivation solution. This solution, consisting of zinc dihydrogen phosphate, 85% phosphoric acid, and zinc nitrate, is combined with quaternized lignin to form a dense, uniform, and moisture-resistant, acid-resistant, or high-chloride-ion-resistant anti-corrosion outer film.

[0004] To achieve the above-mentioned process effects, the technical solution of the present invention is as follows: a zinc diffusion composite passivation solution, based on the total mass of the main components being 100 parts, the composite passivation solution includes 30-40 parts of zinc dihydrogen phosphate, 3-5 parts of 85% phosphoric acid, 8-15 parts of zinc nitrate, 0.1-0.3 parts of quaternized lignin, 0.2-0.5 parts of accelerator, 1-2 parts of complexing agent, and the remaining water.

[0005] Furthermore, based on a total mass of 100 parts for the main components, the composite passivation solution comprises 32-38 parts of zinc dihydrogen phosphate, 3.5-4.5 parts of 85% phosphoric acid, 9-14 parts of zinc nitrate, 0.1-0.3 parts of quaternized lignin, 0.25-0.45 parts of accelerator, 1-2 parts of complexing agent, and the remaining water.

[0006] A preferred technical solution is that the accelerator is sodium nitrite.

[0007] The preferred technical solution is that the complexing agent is one or more of tartaric acid, citric acid and phytic acid.

[0008] The preferred technical solution is that the complexing agent is tartaric acid and phytic acid in a mass ratio of (4~6):1, or the complexing agent is citric acid and phytic acid in a mass ratio of (4~6):1.

[0009] A preferred technical solution is that the quaternized lignin is obtained by modification with alkali lignin and 3-chloro-2-hydroxypropyltrimethylammonium chloride in a mass ratio of 1:(0.7~0.8).

[0010] A preferred technical solution is that the composite passivation solution further includes lanthanum nitrate, and the amount of lanthanum nitrate added is 1 to 2 parts.

[0011] The second objective of this invention is to overcome the deficiencies in the prior art and provide a method for preparing a zinc diffusion composite passivation solution, comprising the following steps: S1: Dissolve zinc dihydrogen phosphate and zinc nitrate in deionized water to obtain the first composite passivation solution; S2: The free acidity of the first composite passivation solution is adjusted by 85% phosphoric acid, and quaternized lignin, complexing agent and accelerator are added in sequence. Finally, the solution is diluted with deionized water to obtain the composite passivation solution. The free acidity of the composite passivation solution is 0.8~1.5, the total acidity is 30~45, and the pH value is 2.5~3.5.

[0012] A preferred technical solution includes the following step between S1 and S2: S1': Lanthanum nitrate is redissolved in the first composite passivation solution.

[0013] The third objective of this invention is to overcome the defects in the prior art and provide a passivation process for a zinc diffusion composite passivation solution, in which a cleaned workpiece is immersed in the composite passivation solution to form an anti-corrosion outer film, and a zinc diffusion layer is provided on the surface of the workpiece, and the temperature of the composite passivation solution is room temperature.

[0014] The zinc-infiltrated layer has a thickness of 30~120μm; further, the zinc-infiltrated layer has a thickness of 50~80μm. The outer anti-corrosion film has a thickness of 2~6μm.

[0015] The preferred technical solution is that the immersion time of the workpiece is 5 to 10 minutes.

[0016] The advantages and beneficial effects of this invention are as follows: The composite passivation solution, composed of zinc dihydrogen phosphate, 85% phosphoric acid, and zinc nitrate, forms a dense and uniform phosphating film under the action of accelerators and complexing agents. Combined with quaternized lignin, it promotes uniform and smooth deposition of zinc ions, avoiding excessive local deposition, thereby inhibiting the growth of zinc dendrites and further forming a smooth and dense anti-corrosion outer film. The quaternized lignin is electrostatically adsorbed on the surface of the metal workpiece, which also improves the corrosion resistance of the workpiece in humid, acidic, or high chloride ion environments. Detailed Implementation

[0017] The specific embodiments of the present invention will be further described below with reference to examples. These examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.

[0018] Zinc diffusion composite passivation solution Based on a total mass of 100 parts for the main components, the composite passivation solution includes 30-40 parts of zinc dihydrogen phosphate, 3-5 parts of 85% phosphoric acid, 8-15 parts of zinc nitrate, 0.1-0.3 parts of quaternized lignin, 0.2-0.5 parts of accelerator, 1-2 parts of complexing agent, and the remaining water.

[0019] Zinc dihydrogen phosphate is the primary film-forming agent, providing zinc ions (Zn). 2+ ) and phosphate (H2PO4) - Zinc phosphate (Zn3(PO4)2·4H2O) is the "raw material" that constitutes the main body of the phosphate film. It hydrolyzes on the metal surface to generate insoluble zinc phosphate crystals (such as Zn3(PO4)2·4H2O), which constitute the main structure of the film layer.

[0020] Phosphoric acid is used to adjust and maintain acidity; phosphating reactions require a specific acidic environment. Phosphoric acid provides free H+. + It controls the balance between the metal dissolution rate and the formation of the phosphating film. Too high an acidity will hinder film formation, while too low an acidity will result in poor film quality.

[0021] The functions of zinc nitrate are twofold: first, to replenish zinc ions, resulting in a more uniform distribution of zinc in the film; and second, as an oxidizing agent, to accelerate the reaction on the metal surface, rapidly consuming electrons and thus significantly shortening the phosphating time, making the film denser. It can slightly oxidize the surface of a workpiece that has been polished by scratches, generating a very thin and dark-colored oxide or mixed salt film, thereby making the bright color of the scratch visually consistent with the surrounding dark substrate, achieving tonal compensation for microscopic defects on the surface.

[0022] Sodium nitrite is used as the accelerator to speed up the dissolution of the metal surface and the formation of crystal nuclei, thereby reducing the phosphating temperature and shortening the processing time. This is key to achieving medium- and low-temperature phosphating. NO2 - It is the most commonly used accelerator, often used with NO3. - When used in combination, it has a special promoting effect on the formation of film, can reduce the phosphating temperature, reduce the metal potential, and refine the phosphating grains.

[0023] In summary, the principle of balance between "micro-corrosion" and "deposition" is as follows: the zinc (Zn) on the surface of the galvanized workpiece and the free acid (H+) in the solution... + (Mainly from phosphoric acid) The reaction consumes H+ + This causes the pH value at the metal-solution interface to increase; NO3 in zinc nitrate -As an oxidant, it reacts with the [H] produced in the reaction, consuming the hydrogen that would hinder the reaction and allowing the reaction to continue. The increase in the pH value at the interface disrupts the hydrolysis equilibrium of zinc dihydrogen phosphate, causing it to transform into insoluble zinc phosphate, and finally deposits and crystallizes on the metal surface to form a phosphating film.

[0024] It also includes lanthanum nitrate, La 3+ Ions form an extremely thin gel-like layer on the metal surface, providing ample "base" for the growth of phosphating crystals. This allows crystal nuclei to form simultaneously and rapidly, significantly shortening the induction period required for film formation. With sufficient and uniform "base," the phosphating film can grow finer and more uniform grains, resulting in tighter intergranular bonding and a smoother, denser overall film. 3+ The ions also chelate with phytic acid to form complexes that deposit on the surface of the metal substrate. During the corrosion prevention process, lanthanum ions are released. The hydroxide ions generated during NaCl corrosion react with the released lanthanum ions to form lanthanum hydroxide and lanthanum oxide, which fill the corrosion cavities and repair the outer anti-corrosion film.

[0025] The working principle of quaternized lignin: The quaternary ammonium groups and hydroxyl groups on the molecular chain strongly electrostatically adsorb onto the cations on the workpiece surface in acidic media, improving the corrosion resistance of the anti-corrosion film. Furthermore, quaternized lignin promotes uniform and smooth deposition of zinc ions, preventing excessive local deposition and thus inhibiting the growth of zinc dendrites, forming a smooth and dense anti-corrosion film. When quaternized lignin is combined with components such as zinc oxide, it exhibits synergistically enhanced ultraviolet light absorption capacity, improving the anti-aging performance of the anti-corrosion film.

[0026] Lignin itself is a natural polymer with excellent barrier properties, which can effectively prevent water, oxygen and corrosive ions (such as chloride ions) from penetrating the anti-corrosion outer film and contacting the metal surface.

[0027] Preparation of Quaternized Lignin: The alkali lignin was purified by first dissolving it in sodium hydroxide solution and filtering to remove insoluble impurities. The filtrate was then heated to 55°C, and 15% nitric acid was added to adjust the pH to 2. The reaction was maintained until the alkali lignin precipitated completely. Next, the alkali lignin filter cake was filtered and washed with a large amount of deionized water to remove inorganic salts and small-molecule carbohydrates. Finally, the filter cake was freeze-dried. The purified alkali lignin was dissolved in sodium hydroxide to form a solution containing 20% ​​alkali lignin. This solution was mixed with 3-chloro-2-hydroxypropyltrimethylammonium chloride solution, heated to 80°C, and reacted for 3-4 hours, maintaining the pH above 10. After the reaction, the pH of the reaction solution was adjusted to 4, followed by purification, rotary evaporation, and freeze-drying to obtain quaternized lignin solid powder.

[0028] The complexing agent is one or more of tartaric acid, citric acid, and phytic acid. Tartaric acid and citric acid, as small-molecule polyhydroxycarboxylic acids, have precise and well-defined functions. In processes such as phosphating, they inhibit excessive grain growth by complexing metal ions, resulting in a finer and denser film, thereby reducing film weight. They also complex impurity ions in the solution, preventing bath aging and extending service life. The corrosion protection principle of phytic acid is that its active groups react with metal ions to form chelate complexes. These chelate complexes can be deposited on the surface of the metal substrate, thereby improving corrosion resistance. Zinc ions in the composite passivation solution promote the adsorption reaction of phytic acid, forming a thicker phytic acid conversion film on the metal surface. Some zinc ions can form agglomerates of zinc oxide, phytic acid, and zinc complexes, and dope the phytic acid conversion film.

[0029] passivation process The cleaned workpiece is immersed in a composite passivation solution to form an anti-corrosion outer film. A zinc-impregnated layer is applied to the surface of the workpiece. The temperature of the composite passivation solution is room temperature.

[0030] The immersion time for the workpiece is 5-10 minutes. Sufficient time is needed to complete the three-step reaction of etching, deposition, and organic adsorption. Insufficient immersion time will result in thin and incomplete anti-corrosion film, significant exposure of the substrate, poor film adhesion, and detachment with slight friction. Insufficient interface etching will result in zinc phosphate crystals floating only on the zinc-diffused surface, and the film will fall off and expose the substrate after impacts, packaging friction, etc.

[0031] Excessive immersion time leads to an excessively thick anti-corrosion film with large, loose crystals; the passivation solution is a weakly acidic system, and continued immersion after film saturation will cause reverse dissolution corrosion; the zinc-infiltrated substrate is excessively corroded and worn away; prolonged acid etching produces a large amount of zinc salt dust adhering to the film surface, which is difficult to rinse off with water, resulting in a hazy appearance on the workpiece and rendering it unusable; the film layer cracks and peels after drying. Thick and rough zinc phosphate films have high thermal expansion and contraction stress, and cracks appear after drying at 80~120℃, causing rust to appear first at the cracks.

[0032] Example 1

[0033] Based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution comprises 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remainder water. The free acidity of the composite passivation solution is 1.2, the total acidity is 38, and the pH value is 2.8.

[0034] The preparation method of zinc diffusion composite passivation solution includes the following steps: S1: Dissolve zinc dihydrogen phosphate and zinc nitrate in deionized water to obtain the first composite passivation solution; S2: The free acidity of the first composite passivation solution was adjusted by 85% phosphoric acid, and quaternized lignin, citric acid and sodium nitrite were added in sequence. Finally, the solution was diluted with deionized water to obtain the composite passivation solution.

[0035] The passivation process of zinc diffusion composite passivation solution involves immersing the cleaned workpiece in the composite passivation solution to form an anti-corrosion outer film. A zinc diffusion layer is set on the surface of the workpiece. The temperature of the composite passivation solution is room temperature, and the immersion time of the workpiece is 8 minutes.

[0036] Example 2

[0037] Example 2 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts tartaric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0038] Example 3

[0039] Example 3 is based on Example 1, except that the complexing agent is citric acid and phytic acid in a mass ratio of 5:1. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0040] Example 4

[0041] Example 4 is based on Example 3, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 1.2 parts lanthanum nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts complexing agent, and the remaining water. The preparation method of the zinc diffusion composite passivation solution further includes the following step between S1 and S2: S1': Lanthanum nitrate is redissolved in the first composite passivation solution, i.e., zinc dihydrogen phosphate, zinc nitrate, and lanthanum nitrate are dissolved in deionized water to obtain the first composite passivation solution. The passivation process remains unchanged.

[0042] Example 5

[0043] Example 5 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 30 parts zinc dihydrogen phosphate, 3 parts 85% phosphoric acid, 8 parts zinc nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0044] Example 6

[0045] Example 6 is based on Example 4, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 30 parts zinc dihydrogen phosphate, 3 parts 85% phosphoric acid, 8 parts zinc nitrate, 1.2 parts lanthanum nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts complexing agent, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0046] Example 7

[0047] Example 7 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 40 parts zinc dihydrogen phosphate, 5 parts 85% phosphoric acid, 15 parts zinc nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0048] Example 8

[0049] Example 8 is based on Example 4, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 40 parts zinc dihydrogen phosphate, 5 parts 85% phosphoric acid, 15 parts zinc nitrate, 1.2 parts lanthanum nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts complexing agent, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0050] Example 9

[0051] Example 9 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 1.2 parts lanthanum nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 25 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 6 parts zinc nitrate, 0.25 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 1, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 0.05 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts citric acid, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0054] Comparative Example 3 Comparative Example 3 is based on Example 4, except that, based on a total mass of 100 parts for the main components, the zinc diffusion composite passivation solution includes 35 parts zinc dihydrogen phosphate, 4 parts 85% phosphoric acid, 12 parts zinc nitrate, 1.2 parts lanthanum nitrate, 0.05 parts quaternized lignin, 0.3 parts sodium nitrite, 1.5 parts complexing agent, and the remaining water. The preparation method and passivation process of the zinc diffusion composite passivation solution remain unchanged.

[0055] Performance testing of passivated workpieces in both the example and comparative models: 1. Thickness of anti-corrosion outer film: The thickness is measured using a magnetic thickness gauge according to the standard GB / T 4956-2003 "Measurement of thickness of non-magnetic coating on magnetic substrate by magnetic method". Five measurement points are evenly selected for each workpiece, and the average value is taken.

[0056] 2. Corrosion Resistance: A drop test solution (0.17g potassium permanganate and 0.26g hydrofluoric acid dissolved in 1kg distilled water) is dropped onto a circular area (a circular test area with a diameter of 5mm). The time it takes for the solution to change from red to colorless is defined as the drop corrosion time of the film. Five measurement points are evenly taken for each workpiece, and the average value is taken. Principle: When the drop solution dissolves the total anti-corrosion film (including the zinc penetration layer and the outer anti-corrosion film), the exposed substrate reacts rapidly with the hydrofluoric acid in the solution to release hydrogen gas, which reduces the red potassium permanganate in the solution to colorless, causing the color of the solution in the test area to fade.

[0057] 3. Corrosion Resistance: A neutral salt spray test was conducted according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". Test conditions: NaCl concentration 5% (mass fraction), pH value 6.5~7.2, temperature (35±2)℃, spray volume (1.0~2.0) mL / (80cm³). 2 The sample surface was placed at an angle of 15° to 25° to the vertical direction. The time (h) required for white rust (corrosion area ≥ 5%) to appear on the sample surface was used as the evaluation index, and the longer the time, the better the corrosion resistance.

[0058] The performance test results of the examples and comparative examples are as follows:

[0059] The total anti-corrosion film of the sample workpiece includes a zinc-infiltrated layer and an outer anti-corrosion film. The zinc-infiltrated layer is 50 μm thick. The workpiece containing only the zinc-infiltrated layer can withstand 60 hours of salt spray testing.

[0060] The thickness of the anti-corrosion outer film in the examples and comparative examples is 2~5μm.

[0061] Example 2 has comparable anti-corrosion performance to Example 1, but it is more economical to use citric acid.

[0062] Compared to Example 1, Example 3 uses a compound citric acid and phytic acid complexing agent, which improves the anti-corrosion performance.

[0063] Compared to Example 3, the addition of lanthanum nitrate in Example 4 further optimized the anti-corrosion performance.

[0064] Compared to Example 1, Examples 5 and 7 show that insufficient content of zinc dihydrogen phosphate, phosphoric acid, and zinc nitrate negatively impacts the film-forming reaction efficiency and easily leads to uneven or excessively thin anti-corrosion films. Excessive content of these substances results in vigorous reactions, leading to coarse and porous anti-corrosion film crystals. Therefore, both decreasing and increasing the content of zinc dihydrogen phosphate, phosphoric acid, and zinc nitrate in the passivation solution system negatively affect the anti-corrosion performance.

[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A zinc diffusion composite passivation solution, characterized in that, Based on a total mass of 100 parts for the main components, the composite passivation solution comprises 30-40 parts zinc dihydrogen phosphate, 3-5 parts 85% phosphoric acid, 8-15 parts zinc nitrate, 0.1-0.3 parts quaternized lignin, 0.2-0.5 parts accelerator, 1-2 parts complexing agent, and the remaining water.

2. The zinc diffusion composite passivation solution according to claim 1, characterized in that, The accelerator is sodium nitrite.

3. The zinc diffusion composite passivation solution according to claim 1 or 2, characterized in that, The complexing agent is one or more of tartaric acid, citric acid, and phytic acid.

4. The zinc diffusion composite passivation solution according to claim 3, characterized in that, The complexing agent is tartaric acid and phytic acid in a mass ratio of (4~6):1, or the complexing agent is citric acid and phytic acid in a mass ratio of (4~6):

1.

5. The zinc diffusion composite passivation solution according to claim 1, characterized in that, The quaternized lignin was obtained by modification with alkali lignin and 3-chloro-2-hydroxypropyltrimethylammonium chloride in a mass ratio of 1:(0.7~0.8).

6. The zinc diffusion composite passivation solution according to claim 1, characterized in that, The composite passivation solution also includes lanthanum nitrate, and the amount of lanthanum nitrate added is 1 to 2 parts.

7. A method for preparing a zinc diffusion composite passivation solution, characterized in that, Includes the following steps: S1: Dissolve zinc dihydrogen phosphate and zinc nitrate in deionized water to obtain the first composite passivation solution; S2: The free acidity of the first composite passivation solution is adjusted by 85% phosphoric acid, and quaternized lignin, complexing agent and accelerator are added in sequence. Finally, the solution is diluted with deionized water to obtain the composite passivation solution. The free acidity of the composite passivation solution is 0.8~1.5, the total acidity is 30~45, and the pH value is 2.5~3.

5.

8. The method for preparing the zinc diffusion composite passivation solution according to claim 7, characterized in that, The steps between S1 and S2 also include: S1': Lanthanum nitrate is redissolved in the first composite passivation solution.

9. A passivation process for a zinc diffusion composite passivation solution, characterized in that, The cleaned workpiece is immersed in a composite passivation solution to form an anti-corrosion outer film. The surface of the workpiece is provided with a zinc-impregnated layer. The temperature of the composite passivation solution is room temperature.

10. The passivation process of the zinc diffusion composite passivation solution according to claim 9, characterized in that, The immersion time for the workpiece is 5 to 10 minutes.